Information Shocks and Investor Behaviour: A Market Model Event Study of Performance Forecasts in China’s Telecom Industry - Hussain, Sayed Akif; Qiu-Shi, Chen; Hussain, Syed Amer (UW Journal of Management Sciences, 2025)
Purpose: This paper analyzes the market response to annual performance projections announcements at the initial listing of A-share telecom companies in China between 2023 and mid-2025. Design and Methodology: A quantitative approach is employed, which is based on an event-study design. Abnormal returns and accumulation abnormal returns are computed in and around announcement dates, and are focused on the. [-1, +1] event windows. Findings: These findings indicate a high level of asymmetric market response. The abnormal returns caused by bad news are larger and more persistent compared to those caused by good news. The abnormal accumulated bad news returns are approximately -3.4% in the [-1, +1] window. It is increased in the face of macroeconomic uncertainty in early 2024. Evidence indicated that there is anticipatory pessimism in that investors expect to receive bad news at least partially in advance of announcements. Implications: The results outline the contribution of the behavioural aspects to the equity market of china. These findings can help policymakers and investors to learn more about how investors behave in the new financial markets and how they respond to the market.